PENGARUH KONDISI DAN LETAK GEOGRAFIS TERHADAP PERSEBARAN DIALEK BAHASA SUNDA DI JAWA BARAT DAN SEKITARNYA - Mirna Kurniasih; early azhar diwarya; Lia Berliana; Muhamad Nurwahyudin (JURNAL GEOGRAFI, 2023)
ABSTRACTLanguage is a means of daily communication for the community to carry out social activities in the community. Sundanese is the regional language of instruction of Sundanese culture spoken by 42 million people, and is the 2nd most widely spoken regional language in Indonesia with speakers spread across West Java province and its surroundings. Sundanese speakers are so numerous that each region has different dialects due to various factors, one of which is geographical location. To analyze geographical location factors that affect the distribution of Sundanese dialect varieties, a literary method is needed to analyze regional conditions and dialect differences influenced by geographical location. The research method used is a literature study by examining existing phenomena with studies from literature sources and the internet. The purpose of this study is to analyze the influence of geographical location on dialect differences, especially Sundanese whose speakers are in the provinces of West Java and Banten indifferent and geographically separated circumstances. In general, it can be said that the geographical conditions of West Java Province and its surroundings are different, namely the landscape and morphology from the coast to the mountains can create its own dialect according to geographical conditions that should be a factor. influence differences in Sundanese dialects.Keyword: Dialect, Sundanese Language, Distribution of Sundanese Language Dialect